Regulatory decyzji wyborczych. Przyczynek do teorii zachowań wyborczych - Drozdowski, Rafał (Wydział Prawa i Administracji UAM, 1997)
The article is a theoretical background for presentation of the results of research programme named "Matters of Poles - Autumn '95" which was aimed at establishing the most important regulators of electoral decisions. The Author attempts to systematize numerous theoretical concepts relating to the question of preferences and electoral behaviour. One can perceive the problem of dimensions of political decisions (i.e. - electoral decisions) in two ways: firstly - we can assume that the key criterion that permits us to make a distinction between particular dimensions is the criterion of more general character of electoral questions. The second criterion is related to the merits and it permits to isolate three fundamental spheres of political interests and political dilemmas which make the point of electoral debate and the poll itself, so all the questions concerning functioning of political, economic and socio-cultural system.
Regulators of electoral decisions: A contrinution to the theory of electoral behaviour